An Efficient Blockchain Enabled Score Voting with Face Recognition - Madhubala. M, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The security considerations of the votes are based on blockchain technology using cryptographic hashes to secure end-to-end verification. To this end, a successful vote cast is considered as a transaction within the blockchain of the voting application. Therefore, a vote cast is added as a new block (after successful mining) in the blockchain as well as being recorded in data tables at the backend of the database. The system ensures only one-person, one-vote (democracy) property of voting systems. This is achieved by using the voter’s unique face image, which is matched at the beginning of every voting attempt to prevent double voting. The Face Recognition is the study of physical or behavioral characteristics of human being used for the identification of person. So implement real time authentication system using face biometrics for authorized the person for online voting system. This work claims to score voting method and data management challenges in blockchain and provides an improved manifestation of the electronic voting process. Score-based voting methods, also known as range voting or rated voting, are electoral systems where voters are allowed to express their preferences for candidates or options by assigning numerical scores to them. Unlike traditional voting methods where voters choose a single candidate, score-based systems enable voters to provide a more nuanced and detailed assessment of their preferences. It is important here to note that cryptographic hash for a voter is the unique hash of voter by which voter is known in the blockchain. This property facilitates achieving verifiability of the overall voting process. Furthermore, this id is hidden and no one can view it even a system operator cannot view this hash therefore achieving privacy of individual voters.
Keywords: Voting Interface Creation; Add Candidate Details; User Credential; User Verification